Association of DSM-5 Betel-Quid Use Disorder With Oral Potentially Malignant Disorder in 6 Betel-Quid Endemic Asian Populations - Lee, Chien Hung; Ko, Albert Min Shan; Yang, Frances M.; Hung, Chung Chieh; Warnakulasuriya, Saman; Ibrahim, Salah Osman; Zain, R.B.; Ko, Ying Chin (American Medical Association, 2018)
IMPORTANCE Betel-quid (BQ) is the fourth most popular psychoactive agent worldwide. An emerging trend across Asia is the addictive consumption of BQ, which is associated with oral cancer and other health consequences. OBJECTIVE To investigate the validity and pattern of DSM-5-defined BQ use disorder (BUD) and its association with oral potentially malignant disorder (OPMD) among Asian populations. DESIGN, SETTING, AND PARTICIPANTS In-person interviewswere conducted from January 1, 2009, to February 28, 2010, among a random sample of 8922 noninstitutionalized adults from the Asian Betel-quid Consortium study, an Asian representative survey of 6 BQ-endemic populations. Statistical analysis was performed from January 1, 2015, to December 31, 2016. MAIN OUTCOMES AND MEASURES Participantswere evaluated for BUD using DSM-5 criteria for substance use disorder and for OPMD using a clinical oral examination. Current users of BQ with 0 to 1 symptoms were classified as having no BUD, those with 2 to 3 symptoms as having mild BUD, those with 4 to 5 symptoms as having moderate BUD, and those with 6 or more symptoms as having severe BUD. RESULTS Among the 8922 participants (4564 women and 4358 men; mean [SD] age, 44.2 [0.2] years), DSM-5 symptoms showed sufficient unidimensionality to act as a valid measure for BUD. The 12-month prevalence of DSM-5-defined BUD in the 6 study populations was 18.0%(mild BUD, 3.2%; moderate BUD, 4.3%; and severe BUD, 10.5%). The 12-month proportion of DSM-5-defined BUD among current users of BQ was 86.0% (mild BUD, 15.5%; moderate BUD, 20.6%; and severe BUD, 50.0%). Sex, age, low educational level, smoking, and drinking were significantly associated with BUD. Among individuals who used BQ, family use, high frequency of use, and amount of BQ used were significantly linked to moderate to severe BUD. Compared with individuals who did not use BQ, those who used BQ and had no BUD showed a 22.0-fold (95%CI, 4.3-112.4) risk of OPMD (P < .001), whereas those with mild BUD showed a 9.6-fold (95%CI, 1.8-56.8) risk (P = .01), those with moderate BUD showed a 35.5-fold (95%CI, 4.3-292.3) risk (P = .001), and those with severe BUD showed a 27.5-fold (95%CI, 1.6-461.4) risk of OPMD (P = .02). Individuals with moderate to severe BUD who used BQ and had the symptom of tolerance had a 153.4-fold (95%CI, 33.4-703.6) higher risk of OPMD than those who did not use BQ, and those with moderate to severe BUD who used BQ and had a larger amount or longer history of BQ use had an 88.9-fold (95%CI, 16.6-476.5) higher risk of OPMD than those who did not use BQ. CONCLUSIONS AND RELEVANCE This international study gathered data about BQ users across 6 Asian populations, and it demonstrates that DSM-5 symptoms could fulfill a BUD construct. Most current Asian users of BQ already have BUD, which is correlated with risk of OPMD. Among individuals with moderate to severe BUD who used BQ, tolerance and a larger amount or longer history of BQ use are the key symptoms that correlated with enhanced risk of OPMD. These findings play an important role in providing a new indication of an additional psychiatric management plan for users of BQ who have BUD.